Ultrasound for Assessing Disease Activity in IBD Patients: A Systematic Review of Activity Scores. (19th April 2018) - Bots, S; Nylund, K; Löwenberg, M; Gecse, K; Gilja, O H; D'Haens, G
Abstract: Background and Aims: Ultrasound [US] indices for assessing disease activity in IBD patients have never been critically reviewed. We aimed to systematically review the quality and reliability of available ultrasound [US] indices compared with reference standards for grading disease activity in IBD patients. Methods: Pubmed, Embase and Medline were searched for relevant literature published within the period 1990 to June 2017. Relevant publications were identified through full text review after initial screening by two investigators. Data on methodology and index characteristics were collected. Study quality was assessed using a modified version of the Quadas-2 tool for risk of bias assessment. Results: Of 20 studies with an US index, 11 studies met the inclusion criteria. Out of these 11 studies, 7 and 4 studied Crohn's disease [CD] and ulcerative colitis [UC0 activity indices, respectively. Parameters that were used in these indices included bowel wall thickness [BWT], Doppler signal [DS], wall layer stratification [WLS], compressibility, peristalsis, haustrations, fatty wrapping, contrast enhancement [CE], and strain pattern. Study quality was graded high in 5 studies, moderate in 3 studies and low in 3 studies. Ileocolonoscopy was used as the reference standard in 9 studies. In 1 study a combined index of ileocolonoscopy and barium contrast radiography and in 1 study histology was used as the reference standard. Only 5 studies used an established endoscopic index for comparison with US. Conclusions: Several US indices for assessing disease activity in IBD are available; however, the methodology for development was suboptimal in most studies. For the development of future indices, stringent methodological design is required.